2015
DOI: 10.1016/j.jacl.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

National Lipid Association Recommendations for Patient-Centered Management of Dyslipidemia: Part 1—Full Report

Abstract: The leadership of the National Lipid Association convened an Expert Panel to develop a consensus set of recommendations for patient-centered management of dyslipidemia in clinical medicine. An Executive Summary of those recommendations was previously published. This document provides support for the recommendations outlined in the Executive Summary. The major conclusions include (1) an elevated level of cholesterol carried by circulating apolipoprotein B-containing lipopro-teins (non-high-density lipoprotein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
496
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(536 citation statements)
references
References 339 publications
(415 reference statements)
4
496
0
12
Order By: Relevance
“…Because the inclusion criterion was an LDL-C of 155 to 232 mg/dL and the average LDL-C reduction at 1 year was ≈ 23%, we did not have the data to validate or refute the current recommendation for a LDL-C target of 100 mg/dL in some guidelines. 9,10 When LDL-C reductions in the pravastatin group were analyzed as a binary trait, the present analyses suggested that those individuals who derived >30% reduction or >39 mg/dL absolute lowering in LDL-C appeared to derive significant benefit in comparison with placebo. It should be recognized, however, that there was considerable overlap in the observed benefits between this group and those achieving lesser reductions on pravastatin.…”
Section: 2mentioning
confidence: 69%
See 1 more Smart Citation
“…Because the inclusion criterion was an LDL-C of 155 to 232 mg/dL and the average LDL-C reduction at 1 year was ≈ 23%, we did not have the data to validate or refute the current recommendation for a LDL-C target of 100 mg/dL in some guidelines. 9,10 When LDL-C reductions in the pravastatin group were analyzed as a binary trait, the present analyses suggested that those individuals who derived >30% reduction or >39 mg/dL absolute lowering in LDL-C appeared to derive significant benefit in comparison with placebo. It should be recognized, however, that there was considerable overlap in the observed benefits between this group and those achieving lesser reductions on pravastatin.…”
Section: 2mentioning
confidence: 69%
“…Furthermore, clinical guidelines have differed on whether to recommend percentage reductions in LDL-C or specific LDL-C levels among such patients. 1,9,10 To provide practical insights into desirable reductions in LDL-C among these individuals, we also conducted an observational analysis that assessed the relationship between reductions in LDL-C (in relative or absolute terms) and on-treatment LDL-C levels with subsequent clinical events. …”
mentioning
confidence: 99%
“…Separate analyses will be performed for patients with T1DM and T2DM, with an overall analysis of all participants for some efficacy endpoints. The percentage change in calculated LDL-C from baseline to week 24 will be analyzed using a mixed-effect model with repeated measures (MMRM) approach to account for any missing data, using all available post-baseline data within the analysis windows (weeks [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The model will also include fixed categorical effects of treatment group, time point and treatment-by-time interaction, as well as the continuous fixed covariates of baseline LDL-C value and baseline value-by-time point interaction.…”
Section: Primary Analysesmentioning
confidence: 99%
“…Guidelines generally recommend an LDL-C goal of < 70 mg/dL (1.81 mmol/L) and/or a reduction of 50% from baseline in patients with T1DM or T2DM considered to be at high or very-high CV risk [5,14,15]. However, even with the currently available treatments, many patients with DM continue to have persistent lipid abnormalities [16][17][18] and are therefore exposed to a residual risk of CV events.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown importance and/or superiority of non-HDL-C concentration as a predictor of CVD development and as a target for statin-based therapy over LDL-C [3,[7][8][9][10]. Although there remains some controversy as the non-HDL-C superiority was not clear in some studies [2,11], Atherosclerosis Society Expert Dyslipidemia Panel [12] and the National Lipid Association [13] have recommended non-HDL-C also as a primary target of therapy of coronary artery disease. Non-HDL-C has also been shown to correlate more strongly with atherogenic lipoprotein subtractions compared to LDL-C [14].…”
Section: Introductionmentioning
confidence: 99%